SHIFT IN THE MEANING OF COSTS AT THE NGABEN CEREMONY - Purwanti, Dewi Junita; Usman, Ernawaty; Sugianto, Sugianto; Kahar, Abdul (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study aims to uncover the meaning of costs in the Ngaben ceremony in Palu City. A qualitative ethnographic approach was used in the Hindu community in Palu City. The informants were objective. Data were obtained through interviews, observation, and documentation, explained interactively. Costs are understood as sacred offerings to honor ancestors and a manifestation of the sincerity of family yadnya. Costs also serve as a means of collective solidarity through shared contributions. Thus, costs are not only financial but also contain spiritual, symbolic, and social values ​​that strengthen community cohesion and the preservation of minority Hindu traditions in Palu City. These findings emphasize the importance of cultural accounting that accommodates spiritual and social dimensions and supports the preservation of minority Hindu culture. This study presents the view that ritual expenditures reflect religious expressions, social solidarity, and cultural identity.